Differential behavioral response to predator odor in neuropathic pain in mice - Natsi, Amalia; Valkanou, Mary; Anousi, Elissavet; Labrakakis, Charalampos (Frontiers in Pain Research, 2024)
Neuropathic pain, a type of chronic pain caused by injury or disease of the somatosensory system, affects 10% of the general population and is difficult to treat. It is strongly associated with mood disorder comorbidities and impairs quality of life. It was recently suggested that hypervigilance caused by chronic pain might be of advantage in some species, helping them avoid predators during injury when they are most vulnerable. Here, we sought to confirm the hypervigilance hypothesis by using two predator odor (PO) paradigms, one with transient and one with continuous odor presentation. We observed behavioral responses to PO in neuropathic and control mice in an open field setting. We find that neuropathic mice show hypervigilance to PO, confirming previous results. However, we also find increased anxiety responses to neutral odor in neuropathic mice, which manifests as maladaptive pain. This demonstrates that this maladaptive nature of pain could be an evolutionary adaptation aimed at reducing injury induced vulnerability.